2021
DOI: 10.1186/s13550-021-00839-x
|View full text |Cite
|
Sign up to set email alerts
|

Automated liver lesion detection in 68Ga DOTATATE PET/CT using a deep fully convolutional neural network

Abstract: Background Gastroenteropancreatic neuroendocrine tumors most commonly metastasize to the liver; however, high normal background 68Ga-DOTATATE activity and high image noise make metastatic lesions difficult to detect. The purpose of this study is to develop a rapid, automated and highly specific method to identify 68Ga-DOTATATE PET/CT hepatic lesions using a 2D U-Net convolutional neural network. Methods A retrospective study of 68Ga-DOTATATE PET/CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 24 publications
(19 reference statements)
0
24
0
Order By: Relevance
“…However, these first-order features do not necessarily reflect true radiomic features to use the hidden potential of imaging data. Wehrend et al developed a DL algorithm to automatically detect tumor lesions in 68 Ga-DOTA-TATE PET in a study of 125 patients [72]. Despite promising results, high physiological liver uptake and comparably low spatial resolution hamper the diagnostic accuracy of PET with SSTR analogs in the detection of liver lesions, making hybrid imaging with MRI desirable.…”
Section: Neuroendocrine Tumorsmentioning
confidence: 99%
“…However, these first-order features do not necessarily reflect true radiomic features to use the hidden potential of imaging data. Wehrend et al developed a DL algorithm to automatically detect tumor lesions in 68 Ga-DOTA-TATE PET in a study of 125 patients [72]. Despite promising results, high physiological liver uptake and comparably low spatial resolution hamper the diagnostic accuracy of PET with SSTR analogs in the detection of liver lesions, making hybrid imaging with MRI desirable.…”
Section: Neuroendocrine Tumorsmentioning
confidence: 99%
“…This area has been more extensively studied for 18 F-FDG PET/CT[ 110 , 111 ]. A retrospective 2021 study retrospectively demonstrated that deep learning could facilitate the automation of detection of hepatic metastases, though future studies with larger sample sizes are required for further validation[ 112 ]. Continued optimization of imaging techniques and development of more selective tracers will continue to improve diagnostic yield and ability of functional imaging to guide the management of GEP-NENs effectively.…”
Section: Imaging Modalitiesmentioning
confidence: 99%
“…However, these firstorder features do not necessarily reflect true radiomic features to use the hidden potential of imaging data. Wehrend et al developed a DL algorithm to automatically detect tumor lesions in 68 Ga-DOTA-TATE PET in a study of 125 patients [72]. Despite promising results, high physiological liver uptake and comparably low spatial resolution hamper the diagnostic accuracy of PET with SSTR analogs in the detection of liver lesions, making hybrid imaging with MRI desirable.…”
Section: Neuroendocrine Tumorsmentioning
confidence: 99%